Surface Engineering of Graphene - Sahoo, Sumanta; Tiwari, Santosh Kumar; Nayak, Ganesh Chandra; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the state of the art in the processing, properties, and applications in various fields of science and technology related to graphene and its derivatives. It also discusses the limitations and drawbacks of graphene due to some of its intrinsic properties. Further, it provides a brief overview of graphene analogs, comparing the properties of graphene with those of other similar 2D materials.
Chapter 1. Present Status and prospect of graphene research -- Chapter 2. Advanced Graphene Materials: Properties & Applications -- Chapter 3. Graphene & its Derivatives for Secondary Battery Application -- Chapter 4. Recent progress in graphene research for the solar cell application -- Chapter 5. Graphene and its Modifications for Supercapacitor Applications -- Chapter 6. Functionalization of Graphene - A Critical Overview of its Improved Physical, Chemical and Electrochemical Properties -- Chapter 7. Synthesis and properties of Graphene and Graphene Oxide based polymer Composites -- Chapter 8.Application of graphene derivatives in Perovskite Solar Cells -- Chapter 9. Graphene and graphene oxide as nanofiller for polymer blends -- Chapter 10. Facile Room-Temperature Synthesis of Reduced Graphene Oxide as Efficient Metal-Free Electrocatalyst for Oxygen Reduction Reaction.
Keywords: Nanotechnology; Surfaces (Technology).; Thin films; Materials; Nanotechnology; Surfaces, Interfaces and Thin Film; Materials Engineering